Long‐term outcomes of cardiac resynchronization therapy in adult congenital heart disease. Issue 6 (17th April 2019) - Leyva, Francisco; Zegard, Abbasin; Qiu, Tian; de Bono, Joseph; Thorne, Sara; Clift, Paul; Marshall, Howard; Hudsmith, Lucy
Abstract: Background and Aims: Randomized, controlled trials of cardiac resynchronization therapy (CRT) excluded patients with adult congenital heart disease (ACHD). We sought to explore long‐term clinical outcomes. Methods and Results: In this single‐center, observational study, events were collected from hospital records on patients with structural ACHD (sACHD) and adults with ischemic (ICM) or nonischemic (NICM) cardiomyopathy undergoing CRT. Patients with sACHD (n = 23, age: 41.6 ± 13.5 years [mean ± standard deviation]) and adults with ICM (n = 533) or NICM (n = 458) were followed‐up for 4.1 years (median; interquartile range: 2.2‐6.1). Total mortality was 5/23 (21.7%; 4.4 per 100 person‐years) in sACHD, 221/533 (41.5%; 11.8 per 100 person‐years) in ICM, and 154/458 (33.6%; 9.7 per 100 person‐years) in NICM. In univariate analyses, total mortality in sACHD was lower than in ICM (hazard ratio [HR]: 0.38; 95% confidence interval [CI] 0.15‐0.91), but similar to NICM (HR: 0.48, 95% CI 0.20‐1.16). Cardiac mortality in sACHD was similar to ICM (HR: 0.78, 95% CI 0.32‐1.92) and NICM (HR: 1.12, 95% CI 0.45‐2.78). Heart failure (HF) hospitalization rates were similar to ICM (HR: 0.44, 95% CI 0.11‐1.77) and NICM (HR: 0.75, 95% CI 0.18‐3.08). In multivariate analyses, no differences emerged in total mortality, cardiac mortality, or HF hospitalization between sACHD and NICM or ICM, after adjustment for age, sex, New York Heart Association class, diabetes, atrial rhythm, QRS duration, QRS morphology, systemic ventricular ejection fraction, and medical therapy. Conclusion: Total mortality, cardiac mortality, and HF hospitalization after CRT in patients with sACHD was similar to adults with ICM or NICM.